Qualitative Investigation of Discontinuous Dynamical Systems on a Plane by the Method of Pointwise Mappings - Urmanchev, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
For two-dimensional discontinuous dynamical systems, we investigate properties of the Poincaré map by the method of pointwise mappings and establish a criterion for the stability of n-impulse cycles and an estimate for the number of sinks.